The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0213509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate factors on height growth of Pinus sylvestris var. mongolica

Abstract: Tree height growth is sensitive to climate change; therefore, incorporating climate factors into tree height prediction models can improve our understanding of this relationship and provide a scientific basis for plantation management under climate change conditions. Mongolian pine (Pinus sylvestris var. mongolica) is one of the most important afforestation species in Three-North Regions in China. Yet our knowledge on the relationship between height growth and climate for Mongolian pine is limited. Based on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
1
10
0
4
Order By: Relevance
“…As predicted, increased temperature generally had a positive effect on tree height growth when water availability was not limiting (Adams 2007;Cortini et al 2011;Sharma and Parton 2018;Zhou et al 2019).…”
Section: Discussionmentioning
confidence: 64%
“…As predicted, increased temperature generally had a positive effect on tree height growth when water availability was not limiting (Adams 2007;Cortini et al 2011;Sharma and Parton 2018;Zhou et al 2019).…”
Section: Discussionmentioning
confidence: 64%
“…mongolica Litv.) in the three northern regions of China, it was found that, as a rule, the height growth of pine trees increased with increasing average monthly temperature in May and the amount of precipitation from October to April, and decreased from increased precipitation in the previous growing season (Zhou et al 2019). Also, a significant positive correlation of the height growth indices of Scots pine with May temperatures was noted by scientists conducting studies in Latvia (Janson et al 2013b).…”
Section: Resultsmentioning
confidence: 93%
“…One of the main types of pine response to various environmental conditions is its linear growth (=height growth). Its variability is closely related to climatic factors and ecological conditions (Koukhta 2003(Koukhta , 2009Chernogaeva and Kuhta 2018;Jansons et al 2013a, b;Pozdnyakova et al 2019;Zhou et al 2019). The height growth of Scots pine in cold and moist regions has been limited by temperature in the previous summer and length of the growing period (McCarroll et al 2003;Pensa et al 2005;Salminen and Jalkanen 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Pinus sylvestris var. mongolica naturally distributed in Honghuaerji, as the main afforestation tree species, was first introduced to Zhanggutai, Liaoning Province, China (Zhou et al, 2019), which has been successfully promoted in more than 300 counties in 13 provinces and regions. According to the results of the eighth forest resource inventory (2009)(2010)(2011)(2012)(2013), the area of Pinus sylvestris var.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%